Music Fusion Bookstore / Doy Hashim, Maria Anna Abd Malik, Kartina Shahardin... [et.al] - Hashim, Doy; Abd Malik, Maria Anna; Shahardin, Kartina; Wan Ramli, Wan Mohd Idham; Zulkifli, Nadira (Faculty of Artistic and Creative Technology, 2006)
Fusion means mixing or uniting different things into one. That is die reason why we name our bookstore Music Fusion since it is the only bookstore that sells music books with all kinds of genre, such as Jazz, Classical, R&B, Rock and others. It is a partnership business that consists of five partners.